Analisis Strategi Guru dalam Mengatasi Kejenuhan Belajar pada Pembelajaran Daring Siswa Kelas IV di SD Negeri Pasarkemis III - Gumilar, Aris; Imaniah, Ikhfi; Ustianingsih, Laysia (ARZUSIN, 2022)
Learning saturation is a person's psychological condition in the form of boredom and excessive fatigue, resulting in a lack of enthusiasm to carry out learning activities. If the student loses the spirit of learning and motivation in learning, the student will be saturated in learning. The large number of tasks at school makes students feel saturated and often ignores tasks. The focus of the research is to analyze teacher strategies in overcoming learning saturation during the online learning period. This study aims to find out what are the teacher's strategies in overcoming student learning saturation during the online learning period of class IV A. The method used is descriptive qualitative by using data collection techniques in the form of observation, interviews, and documentation. Data obtained using data collection, data reduction, data presentation and drawing conclusions. Based on data analysis, teacher strategies were obtained in overcoming learning saturation during the pandemic by applying various methods, approaching parents and students such as home visit activities and evaluating each end of learning by providing motivations to students.